Studi Patologi Kejadian Cysticercosis pada Tikus Putih - Berata, I Ketut; Arjana, Anak Agung Gde; Sudira, I Wayan; Merdana, I Made; Budiasa, I Ketut; Oka, Ida Bagus Made (Jurnal Veteriner, 2010)
Rats are commonly used as animal model in pathological and reproduction research, butunfortunately they are often infected with cysticercosis. The objective of this research was to determinethe pathological changes the of the rats (Rattus novergicus) tissues affected with cysticercus. Thisresearch using 24 of female rats. They were adapted to a new environment for a week and the feeding andwater were provided ad libitum. At the end of adaptation period rats were necropsied and the visceralorgans were examined for pathological changes especially the present of cysticercosis. The liver and kidneyof each rat were soaked in 10% phosphate buffered formalin. Following dehydration process, tissue wereembedded in paraplast, cut at 5 micron and stained with Harris hematoxylin eosin (HE). The resultshowed that 8 of 24 rats were affected by cysticercosis on the liver. The histopathological changes werenecrotic lesions and eosinophylic cells infiltration around the cysticercosis lesion. The results showed that8 of 23 rats were affected by cysticercosis. The presence of necrosis and cells inflammation could interferethe results of the study when such a rats are used. It is therefore necessary to screen rats for cysticercosis.
Keywords: Prevalence, Histopathology, Cysticercosis, Necrose